Persimpangan Etika, Materialisme, dan Branding dalam Iklan Televisi Produk Konsumen - Bayu Erlangga; Nadia Nailun Naja; Nurul Isnaini; Sinta Nuriyah; Miftahul Huda (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2025)
This research discusses the role of television advertising as a medium for conveying cultural and ethical values ​​in consumer society. Through a semiotic analysis approach, this study highlights how messages in advertising implicitly and explicitly encourage consumption patterns and construct a social reality that associates happiness and success with material possessions. In addition, branding strategies in advertising are proven to play an important role in shaping consumer identity through the emotional associations built between products and lifestyle. However, advertising practices often ignore ethical principles such as honesty, fairness and social responsibility, especially towards vulnerable groups. The results of this research emphasize the importance of integrating ethical values ​​in the advertising creative process and increasing public media literacy in order to create a healthier and more sustainable communication environment.